Developing the export potential of a region - Dokashenko, Olga V. Burdyugova, Elena V. Shestakova, Rinad M. Prytkov, Liudmila V. (Opción, 2019)
The research objective is to elaborate the theoretical-methodological provisions and methodological tools for creating the model of a regional export potential development and their practical approbation. The research identifies the factors influencing the development of the country’s economic potential, in which a significant role is played by the export potential of its regions. In conclusion, one of the key prospective directions of export development is an active transition to complex forms of cooperation, comprising the whole innovative-reproduction vertical under import substitution.